Functionally and phylogenetically diverse plant communities key to soil biota. Issue 8 (1st August 2013) - Milcu, Alexandru; Allan, Eric; Roscher, Christiane; Jenkins, Tania; Meyer, Sebastian T.; Flynn, Dan; Bessler, Holger; Buscot, François; Engels, Christof; Gubsch, Marlén; König, Stephan; Lipowsky, Annett; et al.
Abstract : Recent studies assessing the role of biological diversity for ecosystem functioning indicate that the diversity of functional traits and the evolutionary history of species in a community, not the number of taxonomic units, ultimately drives the biodiversity–ecosystem‐function relationship. Here, we simultaneously assessed the importance of plant functional trait and phylogenetic diversity as predictors of major trophic groups of soil biota (abundance and diversity), six years from the onset of a grassland biodiversity experiment. Plant functional and phylogenetic diversity were generally better predictors of soil biota than the traditionally used species or functional group richness. Functional diversity was a reliable predictor for most biota, with the exception of soil microorganisms, which were better predicted by phylogenetic diversity. These results provide empirical support for the idea that the diversity of plant functional traits and the diversity of evolutionary lineages in a community are important for maintaining higher abundances and diversity of soil communities.